Legitimate and Illegitimate Political Self-entrenchment and Its Impact on Political Equality - Kouroutakis, Antonios (De Gruyter, 2021)
Self-serving politicians and self-entrenchment of the political establishment is a diachronic problem tantalizing liberal democracies. Incumbent political actors around the world constantly purport to entrench not only their presence in the political arena, but also their power and as a result, barriers to entry to new political actors are set, the chain of the democratic choice is disrupted and equality of opportunity is distorted. This article focuses on the available means in the constitutional system in order to safeguard a level playing field in the political arena. To this end, this article has three scientific objectives. First, it elaborates on the significance of equality of opportunities in the political system. Second, it identifies how political self-entrenchment creates an uneven playing field. Third, it focuses on the remedies that exist in the constitutional system and examines both legal and quasi legal mechanisms. With an analysis on the current means that are available in the constitutional system, the judicial review, and the alternative political processes based on independent bodies and quasi-judicial mechanisms, this article concludes that self-entrenchment and self-serving politicians are mainly left to be resolved by political means, the so called self-corrective promise of politics.
Keywords: Self-entrenchment; Political equality; Legal safeguards; Political safeguards; Level playing field; 56 Ciencias Jurídicas y Derecho; ODS 16 - Paz, justicia e instituciones sólidas